2010
DOI: 10.1177/1753465810371484
|View full text |Cite
|
Sign up to set email alerts
|

Can immunogenetics illuminate the diverse manifestations of respiratory infections?

Abstract: Improved technologies for high-throughput genotyping and the establishment of well-defined cohorts prompted hope that polymorphisms would be discovered that define a patients' risk of respiratory disease or aid in diagnosis. Genetic pitfalls encountered in this quest include genotyping errors, ethnic differences and linkage dysequilibrium. Differences in the definition of the disease phenotype also create discrepancies, so immunogenetic testing has not yet reached the clinic. However, associations between a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 120 publications
0
7
0
Order By: Relevance
“…However, these studies often provided conflicting results 9 10 . Some of the problems of such studies included low study power, high risk of publication bias, differences in study designs, especially cases and controls recruitment schemes, which altogether led to often bias and confounding, genotyping inaccuracies, and substantial problems in phenotype definition, especially in the case of tuberculosis 11 12 13 . The entire field was plagued by very unfavourable effect-to-bias ratios, a situation in which the magnitude of bias exceeds that of the sought effect 14 .…”
mentioning
confidence: 99%
“…However, these studies often provided conflicting results 9 10 . Some of the problems of such studies included low study power, high risk of publication bias, differences in study designs, especially cases and controls recruitment schemes, which altogether led to often bias and confounding, genotyping inaccuracies, and substantial problems in phenotype definition, especially in the case of tuberculosis 11 12 13 . The entire field was plagued by very unfavourable effect-to-bias ratios, a situation in which the magnitude of bias exceeds that of the sought effect 14 .…”
mentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNP) affecting cytokines, chemokines and their receptors may influence development of an IRD event via effects on HIV disease, on TB itself or on the response to ART [10]. We evaluated single nucleotide polymorphisms (SNP) in inflammatory and other immune-related genes selected based on a literature search for laboratory evidence of functional consequences for an allele and associations with autoimmune disorders, infectious diseases, respiratory and mycobacterial diseases [1]. Here we present the associations of immune-related genotypes on the risk of developing IRD in TB patients.…”
Section: Introductionmentioning
confidence: 99%
“…A complete review of all reported genetic associations with CAP is beyond the scope of this review but can be found elsewhere. 15,16 To illustrate the problems with genetic studies in this area it is worth reviewing the data for the best described genetic risk factors for CAP (as distinct from sepsis in general), which are in the immunoglobulin G2 (IgG2) receptor and in IL-10.…”
mentioning
confidence: 99%